ROLE OF MATERNAL EDUCATION & OCCUPATION IN THE NUTRITIONAL STATUS OF UNDER THREE CHILDREN - Vyas, Shaili; Kandpal, S D; Semwal, Jayanti (Indian Journal of Community Health, 2011)
Research question: To determine the role of Maternal Education & Occupation in the nutritional status of <3yrs children. Objectives: To assess the role of maternal education & occupation in the nutritional status of <3yrs children. Study design: Cross sectional study. Settings:In the field practice area of Department of Community Medicine, Dehradun. Participants:500 children between 0-3years. Statistical Analysis:Chi Square . Results: Majority of mothers (41.20%) were found to be illiterate & of these majority had undernourished children (73.30%). In our study, most (92.20%) of the mothers were housewives or were unemployed ,whereas maximum undernutrition (88.46%) was found in children whose mothers were unskilled labourer by occupation, whereas children of housewives were found to be only 59.22% undernourished.